Federal Sentencing in the Wake of Guidelines: Unacceptable Limits on the Discretion of Sentencers - Freed, Daniel J. (The Yale law journal, 1992)
The federal sentencing process has long been characterized by dynamic relationships between judges and others who exercise powerful discretion in shaping criminal sanctions for convicted offenders. The implementation of the Federal Sentencing Guidelines has altered these relationships in ways not anticipated by Congress or the United States Sentencing Commission, and not recognized by many judges